Heart graft preservation technics and limits: an update and perspectives - Ughetto, Aurore; Roubille, François; Molina, Adrien; Battistella, Pascal; Gaudard, Philippe; Demaria, Roland; Guihaire, Julien; Lacampagne, Alain; Delmas, Clément (Frontiers in Cardiovascular Medicine, 2023)
Heart transplantation, the gold standard treatment for end-stage heart failure, is limited by heart graft shortage, justifying expansion of the donor pool. Currently, static cold storage (SCS) of hearts from donations after brainstem death remains the standard practice, but it is usually limited to 240 min. Prolonged cold ischemia and ischemia-reperfusion injury (IRI) have been recognized as major causes of post-transplant graft failure. Continuous ex situ perfusion is a new approach for donor organ management to expand the donor pool and/or increase the utilization rate. Continuous ex situ machine perfusion (MP) can satisfy the metabolic needs of the myocardium, minimizing irreversible ischemic cell damage and cell death. Several hypothermic or normothermic MP methods have been developed and studied, particularly in the preclinical setting, but whether MP is superior to SCS remains controversial. Other approaches seem to be interesting for extending the pool of heart graft donors, such as blocking the paths of apoptosis and necrosis, extracellular vesicle therapy, or donor heart-specific gene therapy. In this systematic review, we summarize the mechanisms involved in IRI during heart transplantation and existing targeting therapies. We also critically evaluate all available data on continuous ex situ perfusion devices for adult donor hearts, highlighting its therapeutic potential and current limitations and shortcomings.